Synergistic Silver Extraction from Hydrochloric Acid Solutions with Triisobutylphosphine Sulfide in the Presence of Organic Proton-Donor Additives. Issue 1 (2nd January 2019) - Fleitlikh, I.Yu.; Grigorieva, N.A.; Pavlenko, N.I.; Kondrasenko, A.A.; Tikhonov, A.Ya.; Logutenko, O.A.
ABSTRACT: Silver chloride extraction from hydrochloric acid solutions with triisobutylphosphine sulfide (CYANEX 471, L) in the presence of organic proton-donor additives (HR) was studied. Both alkyl-, bromo-, nitro-substituted phenols, and organic acids of various structures were used as additives. A new synergistic effect ( S ) was found to take place in the presence of the additives. The degree of the synergistic effect in the systems containing phenols decreases in the series 4-nitrophenol > 4-bromophenol > 4- tert -butylphenol > 2, 6-dimethylphenol > 2-methyl-6-cyclohexylphenol > 2, 6-bis( tert -butyl) phenol. In the systems containing organic acids, the following series is observed: dinonylnaphthalenesulfonic acid (DNNSA) > 4- tert -butylphenol > caprylic acid > di(2-ethylhexyl)phosphoric acid > bis(2, 4, 4-trimethylpentyl)phosphinic acid. Based on the analysis of the extraction data and the IR and NMR spectra of the extracts, it was concluded that an increase in the silver extraction with CYANEX 471 in the presence of HR is due to the formation of the compound [AgCl∙2L∙HR] in the organic phase. It was shown that a mixture of CYANEX 471 and 4- tert -butylphenol can be used for the highly selective extraction of silver from hydrochloric acid solutions containing metal impurities (Ni, Cu, Co, Zn, Fe(III), and Na). The mixtures of CYANEX 471 with alkylphenols or DNNSA, in which the high synergistic effects ( S ≥ 10 and ≥ 50, respectively) take place, can efficiently be used for processing different industrial silver chloride solutions.